Survival Outcome and Treatment Strategies in Advanced Stage (III‐IV) Laryngeal Cancers at Two European Centers. (23rd August 2013) - Karlsson, Therese R.; Al‐Azzawe, Mohammed; Aziz, Luaay; Hurman, David C.; Finizia, Caterina A.
Abstract : Objectives: In light of continued uncertainty regarding efficacy of treatment of stage III and stage IV laryngeal tumors, this study aims to evaluate organ preservation strategies, comprising radiotherapy and chemoradiotherapy versus surgical treatment (laryngectomy± adjuvant treatment) by encompassing the long‐established practice at two internationally acclaimed tertiary centers not previously presented in published literature. Methods: Retrospective review of non‐randomized prospectively maintained patient databases at two tertiary centers from 1998‐2008; Sahlgrenska University Hospital (SU) in Gothenburg, Sweden, and Aberdeen Royal Infirmary (ARI) in Aberdeen, Scotland. Patients with stage III and IV disease were included in the study. Primary outcome measures included 3‐year overall and disease‐specific survival depending on treatment. Results: A total of 176 patients were identified, of whom 83% were male and 17% were female with an average age of 65. Sixty‐five patients (37%) presented with stage III tumors, of which 51 patients received organ‐preserving treatment and 14 patients underwent total laryngectomy. Corresponding figures for the 111 patients (63%) presenting with stage IV disease were 42 and 69. Three‐year overall and disease‐specific survival for stage III were 58% and 73% respectively. Corresponding figures for stage IV disease were 42% and 53%. Choice of treatment did not significantly influence survival for stage III ( P = 0.56) or IV ( P = 0.93) disease. Conclusions: Choice of treatment, whether it be organ preservation or surgery, does not significantly influence overall or disease‐specific survival. Therefore, other factors such as quality of life and voice and efficacy of salvage treatments are perhaps more likely to indicate preferred treatment options.